Management of Hijaiyah Literacy Learning Based on Ecopedagogy through Loose Parts Media Recycling in Playgroups - Ratu Dinny Fauziah; Zahra Zahra; Tia Putri Pratiwi; Muhammad Rizal (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2026)
This study aims to analyze Hijaiyah literacy learning management based on eco-pedagogy by utilizing recycled loose parts media in Playgroups. The main focus of this study is how spiritual and ecological values are integrated through the planning, implementation, and evaluation stages of learning. Using a descriptive qualitative approach supported by descriptive statistical data, this study involved educators and students as research subjects. Data were collected through structured observations, in-depth interviews, and documentation. The results showed that systematic learning management was able to produce an average child development achievement of 85%. The achievements included the ability to accurately construct Hijaiyah letters and the emergence of eco-literacy characteristics, such as responsibility in treating recycled media. These findings prove that the use of waste as loose parts not only streamlines educational operational costs but is also effective as a pedagogical instrument for introducing the concept of sustainability from an early age. This study recommends the Eco-Religious Literacy management model as an innovative solution for early childhood education in realizing holistic and environmentally friendly learning. Keywords: Learning Management, Hijaiyah, Ecopedagogy, Loose Parts, Early Childhood.